Neuromuscular, perceptual, and temporal determinants of movement patterns in wheelchair fencing: Preliminary study - Borysiuk, Z.; Nowicki, T.; Piechota, K.; Blaszczyszyn, M. (BioMed Research International, 2020)
The objective of the present study was to determine the structure of the movement pattern performed during a wheelchair fencing lunge that is executed in response to visual and sensory stimuli. In addition, a comparison was made between fencers in the categories A and B of disability. In addition, the analysis involved the correlation between the duration of the sensorimotor response and the value of the bioelectric signal recorded in selected muscles. Seven Paralympic team athletes specializing in wheelchair fencing (3 in category A and 4 in category B) participated in the research. The fencers perform at international level competitions and are multiple medalists of the Paralympic Games. In the study, a wireless system for sEMG and accelerometer signal measurement was employed to test the intervals between the initiation of the lunge attack and its termination defined by the touch of the weapon on the coach`s torso. The electrodes were placed on 9 key muscles responsible for the effectiveness of the executed attack: DEL, TRI, BC, ECR FCR, LD, and EAO. The significant intergroup difference in the muscle activation was found to be 0.333 s for category A fencers and 0.522 s for category A fencers at p = 0.039 applies to the latissimus dorsi (LD LT) muscle, which demonstrates its significance as a postural muscle in the structure of the examined movement pattern. In terms of the values of EMG, a tendency for higher MVC (%) values in most muscles for category A competitors was recorded. The latissimus dorsi (DL RT) muscle with an intergroup difference of MVC-114.63 for cat. A and 67.50 for cat. B at p = 0.039 turned out to play a significant role. The results prove the role of postural muscles: external abdominal oblique and latissimus dorsi on the effectiveness of the attacks executed in wheelchair fencing.